Performance status (PS) as a predictor of poor response to immune checkpoint inhibitors (ICI) in recurrent/metastatic head and neck cancer (RMHNSCC) patients. (29th March 2022) - Chalker, Cameron; Voutsinas, Jenna M.; Wu, Qian Vicky; Santana‐Davila, Rafael; Hwang, Victoria; Baik, Christina S.; Lee, Sylvia; Barber, Brittany; Futran, Neal D.; Houlton, Jeffrey J.; Laramore, George E.; Liao, Jay Justin; et al.
Abstract: Background: Anti‐PD1 checkpoint inhibitors (ICI) represent an established standard‐of‐care for patients with recurrent/metastatic head and neck squamous cell carcinoma (RMHNSCC). Landmark studies excluded patients with ECOG performance status (PS) ≥2; the benefit of ICI in this population is therefore unknown. Methods: We retrospectively reviewed RMHNSCC patients who received 1+ dose of ICI at our institution between 2013 and 2019. Demographic and clinical data were obtained; the latter included objective response (ORR), toxicity, and any unplanned hospitalization (UH). Associations were explored using uni‐ and multivariate analysis. Overall survival (OS) was estimated using a Cox proportional hazards model; ORR, toxicity, and UH were evaluated with logistic regression. Results: Of the 152 patients, 29 (19%) had an ECOG PS ≥2. Sixty‐six (44%) experienced toxicity; 54 (36%) had a UH. A multivariate model for OS containing PS, smoking status, and HPV status demonstrated a strong association between ECOG ≥2 and shorter OS ( p < 0.001; HR = 3.30, CI = 2.01–5.41). An association between OS and former (vs. never) smoking was also seen ( p < 0.001; HR = 2.17, CI = 1.41–3.35); current smoking did not reach statistical significance. On univariate analysis, poor PS was associated with inferior ORR ( p = 0.03; OR = 0.25, CI = 0.06–0.77) and increased UH ( p = 0.04; OR = 2.43, CI = 1.05—5.71). There was no significant association between toxicity and any patient characteristic. Conclusions: We observed inferior OS, ORR, and rates of UH among ICI‐treated RMHNSCC patients with ECOG 2/3. Our findings help frame discussion of therapeutic options in this poor‐risk population. Abstract : Relative to those with a performance status of 0‐1, patients with an Eastern Cooperative Oncology Group performance status 2 who received immune checkpoint inhibitors for recurrent/metastatic head and neck cancer have poorer response rates and overall survival as well as increased rates of unplanned hospitalization; no significant difference in toxicity was seen.